THE EFFECTIVENESS OF WEB-BASED LEARNING MEDIA “GAMES TO LEARN ENGLISH” ON YOUNG LEARNERS' VOCABULARY MASTERY - Putri, Niken Amalia Salsabila; Kurniati, Diah; Utomo, Slamet (Applied Research on English Education (AREE), 2025)
Vocabulary is one of the essential parts of language that cannot be separated from learning English. It is challenging to master the four language skills without mastering a vocabulary because it is essential in language learning. The problem of this research is whether web-based learning media Games to Learn English to teach vocabulary to sixth-grade students at SD 1 Ternadi in the 2023/2024 academic year make a significant difference in vocabulary learning. This is an experimental study with one group pre-test and post-test. This study explores the difference in young learners’ vocabulary before and after being taught using web-based learning media Games to Learn English. Only one class in this study as respondents received the treatment as part of this design. The sig (2-tailed) value obtained is 0.00, which is less than 0.05, therefore there is a significant difference. As a result, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, there is a difference between the two values. It is proved that Games to Learn English is effective to teach vocabulary for sixth grade students at SD 1 Ternadi.